Reliability and validity of the Brazilian version of the Hospital Survey on Patient Safety Culture (HSOPSC): a pilot study - Cláudia Tartaglia Reis; Josué Laguardia; Ana Glória Godoi Vasconcelos; Mônica Martins
Abstract: The evaluation of the culture of patient safety in hospitals is nowadays considered as a management too, since it helps to identify problem areas and provide valuable information for planning improvements. This study explored the reliability and validity of the Brazilian version of the Hospital Survey on Patient Safety Culture, an instrument that evaluates characteristics of patient safety culture among hospital staff. The reliability of the instrument was evaluated by analyzing the internal consistency of each dimension. The validity of the tool was carried out by means of exploratory and confirmatory factor analysis. The sample was made up of 322 questionnaires that were collected in two Brazilian hospitals in 2012. Cronbach's alpha ranged from 0.52 to 0.91 for the different dimensions, with the exception of two, for which it was much lower. After excluding four items, the exploratory factor analysis presented adjusted indices that were appropriate for a 10 factor model.